2011
DOI: 10.1136/adc.2010.207845
|View full text |Cite
|
Sign up to set email alerts
|

Can urgency classification of the Manchester triage system predict serious bacterial infections in febrile children?

Abstract: The MTS has poor discriminative ability to predict the presence of SBIs in children presenting with fever to the paediatric ED. Important predictors of SBI are represented within the MTS, but are used in a different way to classify urgency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
16
0
4
Order By: Relevance
“…These studies found that the MTS classified a high percentage of patients with acute coronary syndrome with ST segment elevation as less urgent (Trigo et al, 2008), and the MTS did not predict the presence of severe bacterial infection in children in the emergency department (Nijman et al, 2011). The study selected people with ECG changes as part of the inclusion criteria of the study.…”
Section: Article In Pressmentioning
confidence: 98%
See 2 more Smart Citations
“…These studies found that the MTS classified a high percentage of patients with acute coronary syndrome with ST segment elevation as less urgent (Trigo et al, 2008), and the MTS did not predict the presence of severe bacterial infection in children in the emergency department (Nijman et al, 2011). The study selected people with ECG changes as part of the inclusion criteria of the study.…”
Section: Article In Pressmentioning
confidence: 98%
“…Thirteen articles (59%) evaluated the efficacy of the MTS in a specific group of patients, and studies regarding use of the MTS in children were the most common (Nijman et al, 2011;Seiger et al, 2011). Use of the MTS in patients with clinical conditions such as chest pain, acute coronary syndrome and acute pulmonary embolism was also investigated (Dann et al, 2005;van der Straten et al, 2012).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, a large number of studies were conducted with triage systems to improve their reproducibility in children [10][11][12]14] and to minimize weak aspects and the risks of overtriage [15,28]. However, few of these studies focused specifically on pediatric topics [16]. Our aim was to find a simple and rapid method of evaluating the numerous children who present to the ED with headache.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the MTS in pediatric EDs has been investigated [10][11][12][13][14], but an international debate over the risks of the MTS overtriaging or undertriaging children [15,16], especially infants, is ongoing [10]. Furthermore, the sensitivity and specificity of the MTS in recognizing seriously ill children are questioned [16,17].…”
Section: Introductionmentioning
confidence: 99%